Segmental volumetric analysis with a ventilated or perfused area: identifying the intersegmental plane. (12th November 2022) - Kitazume, Mai; Tane, Shinya; Shimizu, Nahoko; Kitamura, Yoshitaka; Maniwa, Yoshimasa; Nishio, Wataru
Abstract: OBJECTIVES: Two methods are available to identify the intersegmental plane during segmentectomy: the inflation-deflation method, based on the ventilation area, and injection of indocyanine green, based on the pulmonary arterial distribution. However, whether the intersegmental plane created by these 2 methods matches remains unknown. Our goal was to identify the demarcation lines based on bronchial and arterial territories using 3-dimensional computed tomography-based volumetry. METHODS: We collected data from patients who underwent thoracoscopic segmentectomy in our hospital between April 2012 and May 2021. Three-dimensional images were reconstructed from the preoperative contrast-enhanced computed tomography data using the SYNAPSE VINCENT software program. The volume of the affected area and the distance of the tumour from the intersegmental plane were calculated based on each affected artery and bronchus. Each calculated volume was compared to each affected segment using a paired t -test. RESULTS: Of 195 patients, 114 underwent upper lobe segmentectomy, and 81 underwent lower lobe segmentectomy. In upper lobe segmentectomy, the affected arterial segmental volume was smaller than the bronchial volume (505.0 ml vs 539.4 ml, P  < 0.001). In lower lobe segmentectomy, there was no significant difference between arterial and bronchial volumes (234.6 ml vs 236.9 ml, P  = 0.607). The volume of the affected arterial segmental lung and the distance of the tumour from the intersegmental plane were significantly smaller than the bronchial volume in upper lobe segmentectomies. CONCLUSIONS: As per the results, the affected segmental volume delineated by the indocyanine green method would be underestimated in upper lobe segmentectomy. Abstract : During the past 2 decades, segmentectomy has gained popularity among thoracic surgeons.